Evaluating the impact of workstation usage on radiology report times in the initial 6 months following installation...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Tamm EP; Raval B; West OC; Dinwiddie S; Holmes R (Journal of Digital Imaging)
Picture archiving and communications systems (PACS) workstations are reported to improve workflow by making studies immediately available for review upon their completion. This study tested the hypothesis that a workstation would decrease the time from completion of a study to dictation of results (report time). A four-monitor, 2K x 2K workstation (Imation Cemax-Icon, Fremont, CA), was installed in a body imaging computed tomography (CT) reading room. Use of the workstation by the staff radiologists was voluntary. Images were also printed on film and films continued to be hung at the routine hanging times. To evaluate the workstation's maximum impact, data were collected for report times for studies completed during the routine day shift of the staff radiologist (Monday to Friday, 8 AM to 5 PM). Data were collected before workstation installation (August 1997 to November 1997) and for the subsequent 6 months. Histograms of the number of studies (743 v 103) versus report time (mean, 11.7 v 7.4 hours) showed a bimodal distribution, with peaks at approximately 6 and 24 hours, both before (8/97-11/97) and after (6/98) the workstation's installation. However, the number of studies dictated greater than 60 hours (25.2% v 20.4%) and the percentage of studies in the second peak (16 to 48 hours; 4.4% v 0%) both decreased. In conclusion, the workstation decreased the mean (11.7 v 7.4 hours) and standard deviation (19.8 v 9.1 hours) for report times. This was due to a decrease in both the number of cases dictated the day following their completion and the number of outliers (markedly delayed dictations). The decrease in outliers is probably due to a decrease in the number of 'lost' film-based studies. Copyright (c) 1999 by W.B. Saunders Company